Development of intelligent monitoring system for tension overhead line construction based on multi-parameter sensing - Liu-Huo Wang; Qi Xiao; Feng Wang; Xiao-Bin Li; Hua-Shen Guan; Bao-Jun Liu (Discover Applied Sciences)
Abstract Currently, most of the monitoring of the construction process of tension wire construction relies on the experience of the construction personnel, and there are great construction hazards. For this reason, combined with the current physical networking technology, the development of a set of traction machine and tension machine release and tension size, traction walking plate force, and attitude of the danger of allround monitoring. In addition, there is an intelligent monitoring system for tension wire construction with real-time information transmission and warning. After analyzing the construction process and construction procedures of tension wire construction, it is determined that allround safety monitoring of tension wire construction is carried out from the aspects of traction speed of traction machine, traction force of traction machine, release speed of tension machine, tension of tension machine, force of traction walking plate, and tilting angle of traction walking plate, etc., and then it builds up the overall structure of the system’s monitoring points. Aiming at the characteristics of field construction of tension wire, a real-time data collection and processing model is designed, and LoRa communication technology and 4G communication technology are selected to interconnect the self constructed local area network and 4G wide area network, so as to complete the on-site interaction and long distance transmission of data. In view of the characteristics of the system with many types of monitoring volume and wide distribution, the on-site data transmission and early warning program adopts a polling mode to realize the orderly utilization of each channel through time division. The test results indicate that the system has an error of less than 2% for all types of monitoring data. The system was successfully applied to the overhead construction of a 220 kV transmission line in Guangdong in March 2025, completing the monitoring of risk data and effectively ensuring construction safety.